Photonic Wire Bonding as a Novel Technology for Photonic Chip Interfaces - Lindenmann, Nicole (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2018)
To create photonic multi-chip modules, integrated photonic chips need to be connected internally and to external glass fibers. A novel approach to address this task is the concept of photonic wire bonding, where free-standing polymer waveguides are printed in-situ by two-photon polymerization. This book contains a detailed description of the methodology of photonic wire bonding together with a number of key experiments.